Recent Advancements in Supercapacitor Technologies - Rajakumar, G. (Journal of Ubiquitous Computing and Communication Technologies, 2023)
Supercapacitors (SCs) are a form of energy storage that fills the vacuum left by traditional capacitors and batteries. They have greater energy storage capacity than capacitors and can deliver electricity at higher rates than batteries. Both the capacitor and supercapacitor have two electrodes (plates) separated by a dielectric, however super capacitors have electrodes with a larger surface area and thinner dielectrics, allowing for higher energy densities. Super capacitors are extensively employed in portable electronic devices due to its high storage capacity. The design, properties, and uses of supercapacitors are briefly discussed in this article.
Keywords: Supercapacitor; storage capacitor; batteries; electrodes; dielectrics